Analisa Kekasaran Permukaan Besi ST-41 Hasil Pembubutan Lurus Pengaruh Cairan Pendingin Dengan Alat Uji Surface Roughness - Abdilah, Tomi; Sinurat, Fadlah Kaumenni (Rekayasa Material, Manufaktur dan Energi, 2024)
Coolant plays a specific role in the machining process of lathe machines. Aside from extending tool life, in some cases, coolants can reduce forces and refine the surface of the produced products. This research aims to determine the influence of different coolant usage on the surface roughness of cylindrical hinge turning from ST 41 iron. This material was chosen due to its frequent use in machine tooling and its economical price. The research employed an experimental design conducted in the laboratory using a quantitative method. In the process of multi-pass turning, three hinge workpieces were machined using three types of coolants. Hinge workpiece A used pure water coolant, hinge workpiece B used water coolant with the addition of cutting fluid, and hinge workpiece C used lubricant coolant. All three hinge workpieces were machined through cylindrical turning. The results of the research indicate that the average surface roughness values varied among coolants. The lowest average surface roughness was achieved using the water coolant with cutting fluid mixture (1.254 µmm), while the highest was observed with the oil coolant (1.850 µmm). The average surface roughness value for the coolant type was intermediate (1.489 µmm).